INSTRUCTION IN COMMUNICATIVE LANGUAGE AND THE ENHANCEMENT OF COMPETENCIES - Giyasova Dilafruz Xamzayevna,; Shavkatova Hulkar Xasan qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article explores the educational significance of communicative language instruction as an effective pedagogical mechanism for enhancing learners’ competencies in foreign language education. In the context of contemporary methodology, language teaching is no longer viewed as the transmission of grammatical knowledge alone, but as the development of practical communicative abilities, cognitive flexibility, intercultural awareness, and learner autonomy. The study addresses the problem that many learners possess theoretical knowledge of a foreign language but remain unable to apply it effectively in authentic interaction. The research is based on a qualitative pedagogical and theoretical analysis using literature review, conceptual comparison, and methodological interpretation. The study investigates how communicative language instruction contributes to the formation of core competencies such as communicative, linguistic, pragmatic, intercultural, discourse, and collaborative competencies. Special attention is given to the role of authentic tasks, student-centered interaction, feedback systems, and contextualized language use in the competence-building process.